Sustaining Local Values in Character Education: Strategies for Effective Implementation in Community Learning Center Contexts - Eli Farlina; Sri Nurhayati; Agus Hasbi Noor (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study explores the integration and sustainability of local values in character education within the context of Community Learning Centers (CLCs) in Indonesia, focusing on PKBM Melati Batujajar. Employing a case study approach within a qualitative research framework, data were collected through semi-structured interviews, participant observations, and document analysis. The findings reveal the critical role of local values such as "gotong royong" (mutual cooperation), "musyawarah" (deliberation), "kepedulian" (care for others), and "tanggung jawab" (responsibility) in fostering empathy, collaboration, and accountability among learners. These values are integrated into CLC curricula through storytelling, role-playing, collaborative projects, and experiential learning, effectively contextualizing education within the learners' cultural environment. However, challenges such as the lack of standardized curricula, resource constraints, and the influence of globalization pose barriers to sustainability. To address these, the study recommends localized curricula, targeted facilitator training, and community-driven initiatives augmented by digital tools to harmonize tradition with modernity. By bridging the gap between local cultural heritage and contemporary pedagogical practices, this research contributes to the broader discourse on culturally responsive education and provides actionable strategies for preserving local values in non-formal education settings.